Prenatal sonographic diagnosis of Majewski syndrome - Sirichotiyakul S. (2014)
Majewski syndrome is an autosomal recessive disorder characterized by short ribs, polydactyly, short limbs, and a cleft lip. A 26-year-old woman with no family history of genetic diseases presented at 31 weeks' menstrual age with preterm labor and underwent prenatal sonography to screen for fetal anomalies. Sonography revealed a small thorax, markedly short ribs, micromelia, polydactyly, a cleft lip, dolichocephaly, and severe oligohydramnios. The other structures appeared normal. The most likely diagnosis was Majewski syndrome. Vaginal breech delivery was allowed to proceed. The 1,850-g male newborn died of respiratory failure shortly after birth. The postnatal appearance and radiographs confirmed the prenatal diagnosis. © 2002 Wiley Periodicals, Inc.